Comparison of 18F‐florbetaben quantification results using the standard Centiloid, MR‐based, and MR‐less CapAIBL® approaches: Validation against histopathology. Issue 6 (14th May 2019) - Doré, Vincent; Bullich, Santiago; Rowe, Christopher C.; Bourgeat, Pierrick; Konate, Salamata; Sabri, Osama; Stephens, Andrew W.; Barthel, Henryk; Fripp, Jurgen; Masters, Colin L.; Dinkelborg, Ludger; Salvado, Olivier; et al.
Abstract: Introduction: 18 F‐florbetaben is currently approved for the visual rule out of β‐amyloid (Aβ) pathology. It is also used for recruitment and as an outcome measure in therapeutic trials, requiring accurate and reproducible quantification of Aβ burden in the brain. Methods: Data from eighty‐eight subjects (52 male subjects, aged 79.8 ± 10.6 years) who underwent antemortem 18 F‐florbetaben positron emission tomography scan and magnetic resonance imaging less than a year before neuropathological assessment at autopsy were evaluated. Image analysis was performed using the standard Centiloid (CL) statistical parametric mapping approach and CapAIBL ® . Imaging results were compared against autopsy data. Results: Against combined Bielschowsky silver staining and immunohistochemistry histopathological scores, statistical parametric mapping had 96% sensitivity, 96% specificity, and 95% accuracy, whereas magnetic resonance–less CapAIBL standardized uptake value ratioWhole Cerebellum had 94% sensitivity, 96% specificity, and 95% accuracy. Based on the combined histopathological scores, a CL threshold band of 19 ± 7 CL was determined. Discussion: Quantification of 18 F‐florbetaben positron emission tomography scans using magnetic resonance–based and magnetic resonance–less CapAIBL ® approaches showed high agreement, establishing a pathology‐based threshold in CL.